A REVIEW OF RAUWOLFIA TETRAPHYLLA L. : PHOTOCHEMISTRY AND MEDICINAL USES - Arif Hussain Pandith; Naorem Rojita Devi (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2024)
Human beings have encountered diseases since ancient times, and natural products were the primary source of treatments. Plants provide humans with a variety of basic needs, such as food, medicine, shelter, paper, and flavorings. Rauwolfia tetraphylla L., a genus of over a thousand evergreen trees and shrubs in the Apocynaceae family, is crucial in Indian traditional medicine. It is an important ethnobotanical plant with high therapeutic properties that is widely utilized by South Indian tribes. The plant is rich in secondary metabolites, the most prominent being reserpiline, ajmaline, yohimbine, isoreserpine, lankanescine, alstonine, deserpidine, rauvotetraphyllines, sarpagine, and aricine. The assembled data demonstrated that this plant has essential medicinal properties in snakebites, insecticides, high blood pressure, fever, helminthiasis, wound healing, cough, mental diseases, antioxidants, diabetes, anti-inflammatory, antimicrobial, anticancer, piles, vomiting, etc. The present review focuses on the updated information on the phytochemistry and medicinal use of Rauwolfia tetraphylla.